2016
DOI: 10.14411/eje.2016.072
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficiency of traps for horse fly (Diptera: Tabanidae) survey in riparian oak-ash forests in Danube floodplain

Abstract: Abstract. The objective of this work was to evaluate the relative trap effi ciency of the three modifi ed traps baited with 1-octen-3-ol as attractant, Box, Nzi and Canopy, for horse fl y (Tabanidae) survey. Nine traps (three traps per trap type) were tested in 3 × 3 Latin square designs during summer 2011 in riparian oak-ash forests in the Danube fl oodplain of Croatia. Overall, the traps caught 1,986 specimens of 11 horse fl ies species during the study period. The most abundant species caught was Tabanus br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The Tabanidae family are dipterans of veterinary and medical interest. Those that are ectoparasites of horses, prefer dark brown and reddish brown animals (Bassi et al, 2000;Mikuška et al, 2016). Santos et al (2008b) points out that insects can be (2012) highlight that yellow and black may be repellent to some families and attractive to others.…”
Section: Resultsmentioning
confidence: 99%
“…The Tabanidae family are dipterans of veterinary and medical interest. Those that are ectoparasites of horses, prefer dark brown and reddish brown animals (Bassi et al, 2000;Mikuška et al, 2016). Santos et al (2008b) points out that insects can be (2012) highlight that yellow and black may be repellent to some families and attractive to others.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, the Nzi trap consistently caught 4.5 times more tabanids than canopy traps, with a 1.5-fold increase in species richness compared with the canopy trap. The most recently reported study which compared the Nzi trap with other trap types was conducted in Croatia (Mikuska et al 2016). In this study, the relative efficiency of three trap types (Box, Canopy, and Nzi) all baited with octenol as an attractant was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, the Nzi trap significantly outperformed the canopy traps only in an open environment free of trees and brush. Mikuska et al (2016) suggested that these results may be attributed to two features of trap construction and design: trap opening size/position and attractant release rate. Box traps have a 1 m 2 opening on the bottom of the trap and the trap is placed 50 cm above the ground; this large, accessible opening allows tabanids to enter the trap from all sides.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the results of our study, where the Nzi trap collected a mean of 32.6 horseflies per trapping period, while the canopy trap collected 23.8 horseflies per trapping period. Results from trap comparison studies performed in the area of Kopački rit Nature Park, showed that the Nzi traps collected 4.6 times more horseflies than the canopy traps (Mikuška et al ., 2016). Another study in easteren Croatia also confirmed Nzi traps were more efficient in collecting horseflies in comparison with Malaise traps Townes design (1972).…”
Section: Species/traps Modified Box Trap Nzi Trap Malaise Trap Townesmentioning
confidence: 99%
“…However, in the area of Kopački rit Nature Park a very high trapping efficiency of modified box traps was recorded. Modified box traps collected 2.53 times more horseflies than Nzi traps and 11.77 times more than canopy traps (Mikuška et al ., 2016). In our current study, the differences between these traps were considerably lower.…”
Section: Species/traps Modified Box Trap Nzi Trap Malaise Trap Townesmentioning
confidence: 99%